Loan system in Bank Islam Malaysia Berhad: its concepts and operations / Jamaludin Mohamad - Mohamad, Jamaludin (Faculty of Accountancy, 1987)
An Overview on Bank Islam Malaysia Berhad. The idea of setting an Islamic bank in this country was -first started with the establishment of an National Steering Committee on the Islamic Bank in mid 1981 to study, evaluate and coordinate proposals for the establishment o-f an Islamic bank based upon the principals of Syariah (Islamic law) in banking and finance. Being quite different from conventional banking, it was necessary to enact a new legislation to govern the establishment an operation of Islamic bank. Thus, a new act was passed by the Parliament which was then called the Islamic Banking Act on March 11, 1983. The Act, modelled on the existing Banking Act, besides requiring the Islamic Bank to conform to the tenets of Islamic financial practices also requires the bank to comply with prudent banking system...